HUBUNGAN TINGKAT KEMISKINAN DENGAN AKSES PANGAN DI KECAMATAN PARDASUKA KABUPATEN PRINGSEWU - Nurjanah Nurjanah; Suriaty Situmorang; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to analyze the distribution of poor households and analyze the relation between poverty level and household food access. The method used in this research is a survey method. The location was chosen purposively with consideration that Pardasuka Subdistrict represents the highest RASKIN beneficiary area in Pringsewu Regency. The respondents are 67 households of the RASKIN beneficiary selected randomly.  The research data were collected in January 2019. The distribution of poor households was analyzed descriptively and household food access was analyzed by using correlation analysis. The results showed that the distribution of poor households in Pardasuka Subdistrict consists of 47.76% Pre-Prosperous, 19.40% Prosperous I, and 32.84% Prosperous II.  The relation between poverty level and household food access in Pardasuka Subdistrict Pringsewu Regency is negative and significant, which means that when the food access increases, then the poverty level of the poor households decreases.Key words: poor household, food access